Silicon Mobilization in Soils: the Broader Impact of Land Use - Barão, Lúcia (2020)
Dissolved Si (DSi) provision from land systems triggers diatom growth and CO2 sequestration. Soils and ecosystems act as a Si “filter”, transforming DSi originated from mineral weathering into biogenic Si (BSi) after DSi uptake by plants, or into other pedogenic forms of Si (non-BSi). Land use changes the quantity of BSi and non-BSi pools along the soil profile. However, methods used to isolate Si pools include chemical extractions at high temperatures and alkaline environments and therefore are unable to provide information concerning the dissolution potential of BSi and non-BSi pools under normal conditions of temperature and pH. Here, we conducted a batch experiment where forest, pasture and cropland soil samples were mixed with water at 25 °C and pH 7. The soil samples were collected from a temperate land use gradient located in the Belgian Loess Belt. We measured dissolved Si and aluminium (Al) during 80 days. BSi and non-BSi pool contents along the soil profile were known, as they had been established previously through chemical extraction. Results show that BSi and non-BSi enriched samples present distinct Si and Al dissolution curves. While non-BSi pools contribute significantly with immediate availability of Si, BSi pools present an initial slow dissolution. Therefore, croplands that were depleted of phytoliths and had poorly organic horizons display higher concentrations of initial dissolved Si, while pastures and forests, where pedogenic pools dominate only at depths below 40 cm, have more limited initial Si release.